Insights Into Cryoconite Community Dynamics on the Alpine Glacier Throughout the Ablation Season - Tereza Novotná Jaroměřská; Roberto Ambrosini; Dorota Richter; Miroslawa Pietryka; Przemyslaw Niedzielski; Juliana Souza‐Kasprzyk; Piotr Klimaszyk; Andrea Franzetti; Francesca Pittino; Lenka Vondrovicová; Antonella Senese; Krzysztof Zawierucha (Ecology and Evolution)
ABSTRACT Cryoconite holes (water reservoirs) significantly contribute to biodiversity and biogeochemical processes on glacier surfaces. However, the lack of seasonal observations of cryoconite biota limits our knowledge of glacial ecosystem functioning. We studied photoautotrophs, consumers and sediment characteristics (community structure, biomass, elemental composition, organic matter content, δ13C, δ15N) from cryoconite holes in the upper and lower parts of the Forni Glacier ablation zone (Italy) throughout the ablation season. Dominant cyanobacteria were Oscillatoriaceae and Leptolyngbyaceae, while dominant green algae were Zygnemataceae and Chlorellaceae. Tardigrades (Cryobiotus klebelsbergi) were the dominant consumers. The biomass of consumers negatively correlated with the biomass of green algae, indicating that grazing likely controls algal communities in the upper part. Green algae dominated the upper part, while a shift from green algae‐ to cyanobacteria‐dominated communities was observed in the lower part during the season. The increase in δ13C of cryoconite organic matter (OM) in the lower part followed the trend of the community shift of photoautotrophs potentially affected by precipitation. Also, δ13C of tardigrades positively correlated with δ13C of cryoconite OM in the upper part, indicating some cryoconite OM as their food. Some photoautotrophic taxa appeared only on specific dates, and no spatio‐temporal changes in the cryoconite general elemental composition were found. Our data indicate that changes in the community structure and biomass of cryoconite biota on the Forni Glacier likely depend on the interplay between phenology, stochastic events (e.g., rainfall) and top‐down or bottom‐up controls. We demonstrate that multiple observations are essential for understanding the ecology of biota inhabiting cryoconite holes throughout the ablation season.